2005
DOI: 10.1289/ehp.7337
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Creatinine Concentrations in the U.S. Population: Implications for Urinary Biologic Monitoring Measurements

Abstract: Biologic monitoring (i.e., biomonitoring) is used to assess human exposures to environmental and workplace chemicals. Urinary biomonitoring data typically are adjusted to a constant creatinine concentration to correct for variable dilutions among spot samples. Traditionally, this approach has been used in population groups without much diversity. The inclusion of multiple demographic groups in studies using biomonitoring for exposure assessment has increased the variability in the urinary creatinine levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,094
7
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,662 publications
(1,145 citation statements)
references
References 32 publications
39
1,094
7
5
Order By: Relevance
“…Creatinine concentrations in spot urine samples from NHANES III were significantly higher among non-Hispanic blacks as compared with other racial/ethnic groups (Barr et al, 2005); however, race/ethnicity was confounded within sector in our study (Hines et al, 2009). Demographic characteristics such as education, family income, and place of residence have also been associated with concentrations of certain urinary phthalate metabolites in a subset of NHANES III participants (Koo et al, 2002).…”
Section: Discussionmentioning
confidence: 49%
“…Creatinine concentrations in spot urine samples from NHANES III were significantly higher among non-Hispanic blacks as compared with other racial/ethnic groups (Barr et al, 2005); however, race/ethnicity was confounded within sector in our study (Hines et al, 2009). Demographic characteristics such as education, family income, and place of residence have also been associated with concentrations of certain urinary phthalate metabolites in a subset of NHANES III participants (Koo et al, 2002).…”
Section: Discussionmentioning
confidence: 49%
“…We evaluated bivariate associations among FF trace elements, demographic factors, and clinical factors using Spearman correlation coefficients, Wilcoxon rank-sum tests, and Kruskal-Wallis tests as appropriate; we previously reported bivariate associations for urine trace elements [23]. To correct for difference in urine dilution among the women, all urine trace element were adjusted for creatinine [24] and are expressed as μg/g creatinine.…”
Section: Resultsmentioning
confidence: 99%
“…Higher cadmium levels were observed in the children who had higher levels of urinary creatinine, although the creatinine levels were within the range recommended by WHO (1996). It may not be appropriate to draw conclusions from this because of the small study number, but it has previously been identified that creatinine adjustment is not always the most (Miklavčič et al 2011) GM geometric mean, P75 75th percentile, P90 90th percentile, P95 95th percentile, min minimum, max maximum appropriate method for cadmium analysis (Barr et al 2005;Pirard et al 2014). The levels of urinary cadmium in the mothers were low and comparable (within 1 μg/L) with the population-based reference values from a UK study (Bevan et al 2013), the Flemish human biomonitoring program (Milieu Gezondheid 2010) and the US NHANES study (Centers for Disease Control and Prevention 2014, and the German Environmental Survey value for non-smoking adults shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%